Charles Concordia [power engineer biography]. - Kaplan, G.
This paper presents a biography of Charles Concordia. His education, career and contribution to the power engineering field are detailed. In particular, his efforts in the power systems arena are described by the author
Keywords: Charles Concordia; Biography; Career; Education; Power engineer; Power engineering field; Power systems